Regulator of Chromosome Condensation 1-Domain Protein DEK47 Functions on the Intron Splicing of Mitochondrial Nad2 and Seed Development in Maize - Cao, Shi-Kai; Liu, Rui; Sayyed, Aqib; Sun, Feng; Song, Ruolin; Wang, Xiaomin; Xiu, Zhihui; Li, Xiaojie; Tan, Bao-Cai (Frontiers in Plant Science, 2021)
In flowering plants, mitochondrial genes contain approximately 20–26 introns. Splicing of these introns is essential for mitochondrial gene expression and function. Recent studies have revealed that both nucleus- and mitochondrion-encoded factors are required for intron splicing, but the mechanism of splicing remains largely unknown. Elucidation of the mechanism necessitates a complete understanding of the splicing factors. Here, we report the identification of a regulator of chromosome condensation 1 (RCC1)-domain protein DEK47 that is required for mitochondrial intron splicing and seed development in maize. Loss of function in Dek47 severely arrests embryo and endosperm development, resulting in a defective kernel (dek) phenotype. DEK47 harbors seven RCC1 domains and is targeted to mitochondria. Null mutation of DEK47 causes a deficiency in the splicing of all four nad2 introns, abolishing the production of mature nad2 transcript and resulting in the disassembly and severely reduced activity of mitochondrial complex I. In response, the expression of the alternative oxidase AOX2 is sharply increased in dek47. These results indicate that Dek47 is required for the splicing of all the nad2 introns in mitochondria, and essential for complex I assembly, and kernel development in maize.